Electrochemical behaviour of laser solid formed Ti–6Al–4V alloy in a highly concentrated NaCl solution. (September 2018) - Li, Jiaqiang; Lin, Xin; Guo, Pengfei; Song, Menghua; Huang, Weidong
Highlights: The grain characteristics of laser solid forming Ti-6Al-4V is characterized. The corrosion resistance relies on the grain characteristics of the deposit. The electrochemical dissolution is affected by the grain characteristics. The transpassive dissolution potential is determined by phase constituent. Abstract: Grain characteristics exhibit significant effects on electrochemical machining. The effects of the surface of grains on the electrochemical behaviour of laser solid formed Ti-6Al-4V deposits were investigated using a 15 wt.% NaCl solution. The epitaxial growth behaviour caused the deposits to generally exhibit columnar grains near the lateral surface and equiaxed-shape grains near the top surface. The coarser columnar grains presented inferior corrosion resistance, while the equiaxed grains exhibited slightly better corrosion resistance but distinctly poorer electrochemical machinability. The increase in the β/α volume ratio of the grain decreased its corrosion resistance but increased the transpassive dissolution potential.